2019
DOI: 10.1080/25765299.2019.1565193
|View full text |Cite
|
Sign up to set email alerts
|

A novel hybrid approach for solving the multiple traveling salesmen problem

Abstract: The multiple Travelling Salesmen Problem (mTSP) is one of the most popular and important operational research problems. It is a problem where n salesmen have to visit m cities such that each salesman has to visit at least one city and all the cities should be visited exactly once, starting and ending at one specific city. In this paper a new hybrid approach called AC2OptGA is proposed to solve the mTSP. AC2OptGA is a combination of three algorithms: Modified Ant Colony, 2-Opt, and Genetic Algorithm. Ant Colony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…en a hybrid GA (HGA) is developed using a heuristic method for creating initial population, SCX, swap mutation, local search approach, and an immigration approach for finding highquality solution to the reduced problem. e usefulness of our proposed HGA is observed against some ACO-based algorithms [21][22][23], GAs [24,25], and a gravitational emulation approach [26] on some symmetric instances from TSPLIB [27]. e computational experiences demonstrate the usefulness of the proposed HGA.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…en a hybrid GA (HGA) is developed using a heuristic method for creating initial population, SCX, swap mutation, local search approach, and an immigration approach for finding highquality solution to the reduced problem. e usefulness of our proposed HGA is observed against some ACO-based algorithms [21][22][23], GAs [24,25], and a gravitational emulation approach [26] on some symmetric instances from TSPLIB [27]. e computational experiences demonstrate the usefulness of the proposed HGA.…”
Section: Introductionmentioning
confidence: 88%
“…A novel hybrid approach, named AC2OptGA, by combining a modified ACO, 2-opt, and GA is proposed in [21] to find solution to the problem. Initially, solutions are generated using ACO, then enhanced the obtained solutions using the 2-opt method, and finally, once again improved solution quality using GA. is approach is evaluated using various instances from TSPLIB and found better than the existing algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…ACO approaches are used to produce solutions that use the 2-opt edge exchange approach to improve the solutions obtained. The basic concept of using ACO to solve the MTSP is the salesmen on their tours simulate or act like ants in their search for food, they go separately leaving a pheromone in the path they follow while searching for food [8].…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that seeker genetic algorithm obtains a path with the lowest cost. (18) Liao, T.-Y. (2017) proposed details and a crossover meta-heuristic algorithm to address on-line vehicle routing problem, for reducing costs which surrounds financial matters and emissions.…”
Section: Introductionmentioning
confidence: 99%